IDENTIFIKASI JENIS KURA-KURA DI KALIMANTAN BARAT - Anandita Eka Setiadi (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Study on turtles identification in West Kalimantan has been carried out. This study is aimed at determining and identifying spesies of turtlesin West Kalimantan. Furthermore, it is expected to be the first step that will provide basic information to support turtle conservation and management in West Kalimantan. The Methods used were surveys and interviews. The results of this study found 10 individual turtles from Pontianak ,Pontianak regency and Sambas regency. Identification revealed  that there were two spesies of Geomydidae family and one spesies of Emydidae family. The study discovered that Cuora amboinensis and Cyclemys dentata belong Geomydidae family. While Trachemys scripta belongs Amydidae family. Keywords :Turtle, West Kalimantan, Cuora amboinensis,Cyclemys dentata,  Trachemys scripta